PREFERENCE HETEROGENEITY IN COMMERCIAL VEHICLE PASSENGER CHOICE: A DISCRETE CHOICE EXPERIMENT - Baidoo, Isaac K.; Nyarko, Eric; Doku-Amponsah, K.; Nortey, Ezekiel N. N.; Mettle, Felix O. (European Scientific Journal, ESJ, 2015)
The study sought to identify the knowledge of passengers about the characteristics of commercial vehicles that influence passenger’s choice and makes it attractive to private car users. It therefore presents the preference estimates for various attributes that affect commercial vehicles choice, with reference to students in University of Ghana who patronize commercial vehicles from Circle bus station in Accra to Kumasi with the main objective of understanding more about the factors that influence passenger’s choice of commercial vehicles. A discrete choice experiment was designed to capture the responses for estimating passenger’s commercial vehicles choice for various attributes specific to vehicles in the study area, that are loading passengers simultaneously. The main model was generated using the binary probit in STATA which was further segmented according to gender. The magnitude of estimates fromthe probit model indicated that, generally, passengers prefer commercial vehicles with entertainment, very new and almost full with passengers. This was generally supported by the segmented model by gender. Also, passengers will generally trade the size and brand off for very new and commercial vehicles with reduced loading/waiting period.